The influence of taxable entrepreneurs and the rupiah exchange rate on value-added tax revenues in Indonesia - Susilawaty, Tengku Eka; Siregar, Nancy Mayriski; Cheviandri, Rifqy (International Journal of Applied Finance and Business Studies, 2024)
Value-added tax is a type of tax that is the second-largest contributor to income in the taxation system. This research aims to understand and empirically test the determinants of VAT revenue. The research was conducted in Indonesia during the period 1993–2022, with a sample size of 30 observations. The sampling method used was a nonprobability sampling method with a saturated sampling technique, where the entire population was sampled. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis, it is concluded that partially entrepreneurs are taxed and the rupiah exchange rate influences value-added tax revenues. Simultaneously, taxable entrepreneurs and the Rupiah exchange rate together have an influence on VAT revenues.